2000
DOI: 10.1111/1469-8986.3740515
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and enhancement of emotional responses to unpleasant pictures

Abstract: Despite the prominence of emotional dysfunction in psychopathology, relatively few experiments have explicitly studied emotion regulation in adults. The present study examined one type of emotion regulation: voluntary regulation of short-term emotional responses to unpleasant visual stimuli. In a sample of 48 college students, both eyeblink startle magnitude and corrugator activity were sensitive to experimental manipulation. Instructions to suppress negative emotion led to both smaller startle eyeblinks and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
265
3
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 382 publications
(292 citation statements)
references
References 28 publications
20
265
3
4
Order By: Relevance
“…Recent investigations of emotion regulation have shown that conscious attempts to increase and decrease emotion result in modulation of physiological and neural responses to emotional events (DanGlauser & Gross, 2011;Demaree et al, 2004;Dillon and LaBar, 2005;Driscoll et al, 2009;Jackson et al, 2000;Kim and Hamann, 2007;Lee et al, 2009;Mauss et al, 2007;Moser et al, 2006;Ochsner et al, 2004;Ray et al, 2010;Sheppes et al, 2009). For example, increased and decreased facial frown muscle activity were observed during reappraisal to increase and decrease negative emotions, respectively, in line with subjective affect report (Gross, 1998;Ray et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
“…Recent investigations of emotion regulation have shown that conscious attempts to increase and decrease emotion result in modulation of physiological and neural responses to emotional events (DanGlauser & Gross, 2011;Demaree et al, 2004;Dillon and LaBar, 2005;Driscoll et al, 2009;Jackson et al, 2000;Kim and Hamann, 2007;Lee et al, 2009;Mauss et al, 2007;Moser et al, 2006;Ochsner et al, 2004;Ray et al, 2010;Sheppes et al, 2009). For example, increased and decreased facial frown muscle activity were observed during reappraisal to increase and decrease negative emotions, respectively, in line with subjective affect report (Gross, 1998;Ray et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
“…Startle measurement. Affect-modulated startle eye-blink magnitude was measured from silver-silver chloride electromyographic electrodes placed below the eye on the orbicularis oculi muscle in response to an acoustic startle probe (50-ms whitenoise burst at 95 dB with a near-instantaneous rise time) as described by Jackson et al (32). Startle eye-blink magnitude was calculated by subtracting the amount of integrated electromyographic activity at reflex onset from the maximum amount of integrated electromyographic activity between 20 and 120 ms after the probe onset.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the results of this research generally mirror what we have observed in our pain studies. Eyeblinks are facilitated by defensive activation (positive affect) and inhibited by appetitive activation (negative affect) (for reviews, Bradley et al, 1999;Grillon and Baas, 2003), although inhibition by appetitive activation is less robust (Grillon and Baas, 2003;Jackson et al, 2000). This modulation by affective valence 1 (the unpleasantness-pleasantness dimension of affect) is most reliable when the probe onset is between 3 and 5-s after onset of the affectinducing stimulus (3 to 5-s lead interval) (Bradley et al, 1993b(Bradley et al, , 2006, unless the task instructions are altered (e.g., Dichter et al, 2002;Vanman et al, 1996).…”
Section: Affective Modulation Of the Startle Eyeblink Responsementioning
confidence: 99%